Language Strategies Used in a Ward in a Government Hospital to Minimise Language Miscomprehensions - Abesooriya, A.P.L.P; Rassool, R. (University of Jaffna, 2025)
Language is a critical factor in the reception of successful healthcare. Proper understanding of language and instructions is crucial to avoid dire consequences of misinterpretations and misunderstandings. To explore the language strategies used in the healthcare sector in Sri Lanka, a ward from a particular government hospital was selected. Through non-participant observations and semi-structured interviews, it was found that the language associated mainly with spoken aspects in the ward was Sinhala. Even though there were Sinhala and Tamil-speaking patients in the ward, the ward staff doctors, nurses and attendants- used Sinhala to communicate with the patients. The medical instructions, announcements, advice and casual conversations between the parties took place in Sinhala. The Sinhala-speaking doctors, nurses and attendants used Sinhala to communicate with both Sinhala and Tamil-speaking patients. However, it was noted that Tamil-speaking doctors used both Sinhala and Tamil in the ward, depending on the patient’s fluency in the language and the language that they were comfortable with. If the patient was a Sinhala-speaking patient, the Tamil-speaking doctor used Sinhala to communicate with them, while the doctor used Tamil if the patient was a Tamil-speaking patient. It was noted that most of the members of the healthcare staff did not consider the patients’ comfort and language fluency or the language policy in Sri Lanka, whereas they used the language they were comfortable with for communication. Furthermore, as evident, Sinhala being the majority language in the ward, the members in the ward used different strategies to make the non-Sinhala speakers understand the Sinhala language rather than using their comfortable language. The members of the ward used the Tamil-speaking male guardians, Tamil-speaking doctors and Tamil-speaking patients who were equally fluent in Sinhala language as interpreters in the ward to make the other Tamil-speaking patients understand the Sinhala language. Furthermore, the use of ‘deixis’, the use of common and less complex Sinhala words and the use of loanwords were noted as strategies used in the ward. Even though these strategies were used, it was noted that mainly the Tamil population and occasionally the Sinhala population were in a vulnerable situation as the hospital did not adhere to the language policy guidelines of Sri Lanka. It was also noted that the Sinhala and English languages act as symbolic capitals and markers of power, while also reflecting the ideologies and cultures of the members of the ward. The lack of clear-cut language policies and the necessity of solid language policies in healthcare to minimise language barriers are highlighted in the study.
Keywords: Government hospital; Language barrier; Language policy; Language strategies; Sri Lanka